Developing an evidence-based foster mother screening tool for cluster foster care in the Western Cape, South Africa - Simula, Kelebogile (Department of Social Development, 2017)
Within the formal child welfare system in South Africa, foster care is considered the preferred form of alternative care for children removed from their biological families and who are unavailable for adoption. This reflects the belief that the family is ideal environment best suited for optimal child survival and development. Although many South African children have benefitted from court-ordered foster care in the last two decades, however ineffective screening, training and preparation of foster carers have posed challenges to meeting the needs of children in need of alternative care. Utilizing general systems and attachment theories, the purpose of this study was to explore perceptions about developing an evidence-based tool for the screening of eligible foster mothers of children in cluster-foster care in South Africa. The study employed a qualitative research approach to data collection and analysis. A semistructured interview schedule was used to explore the perspectives of 12 social workers and four foster mothers about context-specific criteria for screening foster mothers within the clusterfoster care system in South Africa. Results indicate that a reliable and valid tool for screening eligible mothers in cluster foster care settings in South Africa should include a standardized assessment of parenting skills and psychological wellbeing of potential foster mothers in addition to the normative sociodemographic background assessments. Emotional and financial support were also shown to be crucial in ensuring the retention of foster mothers within the context of high attrition rates of foster parents in South Africa. The findings of this study underscore the importance of using an evidence-based screening tool to recruit potential foster mothers in South Africa and the need to assess the psychosocial wellbeing of potential foster mothers in addition to background checks.